The Impact of Financial Literacy, Digital Innovation, and Marketing Strategy on Business Performance through Financial Record-Keeping Discipline: A Study on MSMEs - Chairunesia, Wieta; Wahyudi, Sely Megawati; Tanjung, Putri Renalita Sutra; Oktasari, Dian Primanita (JAS (Jurnal Akuntansi Syariah), 2025)
Purpose - This study aims to examine the influence of financial literacy, digital innovation, and marketing strategy on MSME business performance, with financial record-keeping discipline as a mediating variable. Method - Using a quantitative approach, data were collected from 100 MSME owners in Bekasi through structured questionnaires using purposive sampling technique and analyzed with Structural Equation Modeling (SEM) using SmartPLS. Findings - The findings reveal that financial literacy and marketing strategy have a positive and significant impact on business performance, both directly and indirectly through record-keeping discipline. In contrast, digital innovation shows no significant direct or indirect effect. These results underscore the importance of integrating knowledge-based resources into consistent managerial practices. Implications - Theoretically, this study extends the Resource-Based View, Financial Literacy Theory, and Digital Capability Theory by highlighting the role of internal processes as mediators. Practically, it emphasizes the need for MSMEs to strengthen financial discipline alongside marketing efforts to achieve sustainable performance improvement.